Relationship between Climate Change and Prevalence of Environmentally Based Diseases in Coastal Fishing Communities in Sambuli Village, Nambo District - Pitrah Asfian; Rifdah Nabiilah; Fitra Sawfla Insani; Keisya Amalia Maharani; Sitti Nurhaliza; Selfin Dwiyanti; ⁠Nur Hidayat; Aulia Mutmainna; Intan Wahid Ingrat; Putri Mentary (Journal of Epidemiology and Health Science, 2025)
Background: Climate change has emerged as a critical global issue, influencing various dimensions of human life, including public health. Its manifestations such as rising temperatures, irregular rainfall patterns, and the increasing frequency of natural disasters like tidal flooding, coastal erosion, and drought pose significant threats to the health and well-being of communities. Coastal populations, particularly those in Sambuli Village, are especially vulnerable due to environmental conditions that are less conducive to health, limited access to clean water, and a general lack of awareness regarding climate change adaptation strategies. Furthermore, the local economy and livelihoods, which predominantly rely on marine resources, are also adversely affected by seasonal and weather-related changes. This study seeks to examine the correlation between climate change and the prevalence of environment-related diseases among coastal fishing communities. Objective: To assess the impact of climate change on the prevalence of environmental-based diseases in coastal fishing communities in Sambuli Village. Methods: This study employed a quantitative analytical approach with a cross-sectional design. Data were obtained from 200 respondents through the administration of structured questionnaires. The collected data were analyzed using univariate and bivariate statistical methods to identify significant associations. Results: Findings revealed that 32.5% of respondents identified erratic rainfall as the most prominent impact of climate change. The most frequently reported illness was fever or influenza, affecting 56.5% of participants. Statistical analysis demonstrated a significant association between perceptions of climate change and the quality of clean water used (p-value < 0.05), suggesting that changes in climate patterns may influence water-related health outcomes. Conclusion: Climate change has a demonstrable effect on the health status of coastal communities. Therefore, adaptive strategies particularly those focusing on environmental hygiene and access to safe water must be strengthened to mitigate health risks and enhance community resilience in the face of ongoing climatic shifts. Keywords: Climate Change, Environmental-Based Diseases, Coastal Communities, Public Health, Adaptation Strategies, Indonesia